Triple Diagnostic Accuracy on Early Stage Breast Cancer at dr. Cipto Mangunkusumo and Persahabatan General Hospital - Kartini, Diani; Megatia, Ika; Darmiati, Sawitri; Rustamadji, Primariadewi; Budiningsih, Setyawati (UI Scholars Hub, 2018)
Introduction. Breast cancer is the most common cancer in Indonesia with incidence rate 40.3 per 100.000 women and mortality rate 16.6 per 100.000women. On early stage, the decision for operative procedure (i.e. mastectomy) requires intraoperative frozen section to assess malignancy; which is mostly unavailable in secondary hospitals. The triple diagnostic (TD) test consists of physical examination, breast ultrasonography and fine needle aspiration biopsy is an accurate and simple preoperative diagnostic method that may solve the problem. The study aimed to find out conformance of the triple diagnostic to histopathology findings in those with breast lump where the malignancy was suspected. Method. A study of diagnostic accuracy conducted enrolling subjects with suspected malignant breast lump managed in dr Cipto Mangunkusumo General Hospital (RSCM) and Persahabatan Hospital (RSP) in period of February 2016 to August 2017 who met the criteria: those underwent preoperative triple diagnostic, intraoperative frozen section and histopathology examination. The conformance of TD and frozen section were compared to histopathology findings. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy were the focuses of the study. Results. There were 33 subjects enrolled (prevalence of 4.3%), mean age of 49.6 years ± 10.9, were above 40 years (78.8%). Tumor size of 2–5 cm found in 63.6% subjects, and the most histopathology finding was invasive carcinoma (84.8%). Frozen section showed sensitivity of 96.8%, specificity of 100%, PPV of 100%, NPV of 66.7% and accuracy of 97.0%. TD showed sensitivity of 77.4%, specificity of 100%, PPV of 100%), NPV of 22.2% and accuracy of 78.8% (p = 0.016). Conclusion. Triple diagnostic reaches up to 78% accuracy on early stage breast cancer may be used secondary hospital in Indonesia whenever frozen section is unavailable.